The Role of Court Excellence in Facilitating Expedited Trials to Enhance Legal Efficiency in Indonesia - T.H. Simarmata, Edward; Achmad Darodjat, Tubagus (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
This scholarly article investigates the implementation of court excellence frameworks as a mechanism for expediting trials, thereby improving legal efficiency within Indonesia's judicial landscape. The Indonesian justice system confronts considerable challenges in delivering timely justice, largely attributed to case backlogs and procedural inefficiencies. Court excellence principles are examined here as a strategic approach to streamline judicial processes, boost institutional efficiency, and accelerate case resolutions. Through an analysis of Indonesia’s legal structures and current practices, this paper underscores the critical role of court excellence principles in fostering a justice system that is both equitable and efficient. Key insights and strategic recommendations are provided to support the effective implementation of expedited trials, ultimately promoting legal expediency in Indonesia.